The relationship between cisplatin resistance and histone deacetylase isoform overexpression in epithelial ovarian cancer cell lines - Kim, Min-Gyun; Pak, Jhang Ho; Choi, Won Ho; Park, Jeong-Yeol; Nam, Joo-Hyun; Kim, Jong-Hyeok (Journal of gynecologic oncology, 2012)
To investigate the relationship between cisplatin resistance and histone deacetylase (HDAC) isoform overexpression in ovarian cancer cell lines. Expression of four HDAC isoforms (HDAC 1, 2, 3, and 4) in two ovarian cancer cell lines, SKOV3 and OVCAR3, exposed to various concentrations of cisplatin was examined by western blot analyses. Cells were transfected with plasmid DNA of each HDAC. The overexpression of protein and mRNA of each HDAC was confirmed by western blot and reverse transcriptase-polymerase chain reaction analyses, respectively. The cell viability of the SKOV3 and OVCAR3 cells transfected with HDAC plasmid DNA was measured using the cell counting kit-8 assay after treatment with cisplatin. The 50% inhibitory concentration of the SKOV3 and OVCAR3 cells can be determined 15-24 hours after treatment with 15 µg/mL cisplatin. The expression level of acetylated histone 3 protein in SKOV3 cells increased after exposure to cisplatin. Compared with control cells at 24 hours after cisplatin exposure, the viability of SKOV3 cells overexpressing HDAC 1 and 3 increased by 15% and 13% (p<0.05), respectively. On the other hand, OVCAR3 cells that overexpressed HDAC 2 and 4 exhibited increased cell viability by 23% and 20% (p<0.05), respectively, compared with control cells 24 hours after exposure to cisplatin. In SKOV3 and OVCAR3 epithelial ovarian cancer cell lines, the correlation between HDAC overexpression and cisplatin resistance was confirmed. However, the specific HDAC isoform associated with resistance to cisplatin varied depending on the ovarian cancer cell line. These results may suggest that each HDAC isoform conveys cisplatin resistance via different mechanisms.